2008
DOI: 10.1017/s0305000908008891
|View full text |Cite
|
Sign up to set email alerts
|

Korean- and English-speaking children use cross-situational information to learn novel predicate terms

Abstract: This paper examines children’s attention to cross-situational information during word learning. Korean-speaking children in Korea and English-speaking children in the US were taught four nonce words that referred to novel actions. For each word, children saw four related events: half were shown events that were very similar (Close comparisons), half were shown events that were not as similar (Far comparisons). The prediction was that children would compare events to each other and thus be influenced by the eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 39 publications
(52 reference statements)
6
51
0
3
Order By: Relevance
“…Developmental research indicates that comparison promotes relational learning in children as well as in adults (Childers & Paik, 2009;Christie & Gentner, 2010;Gentner, Anggoro, & Klibanoff, 2011;Gentner & Namy, 1999;Haryu, Imai, & Okada, 2011;Namy & Gentner, 2002). For example, Gentner, Loewenstein, and Hung (2007) taught 3-, 4-, and 5-year-old children to identify novel object parts; children were shown a novel standard figure, told that "this one has a blicket," and asked to say which of two other figures also had a "blicket."…”
Section: Methodsmentioning
confidence: 99%
“…Developmental research indicates that comparison promotes relational learning in children as well as in adults (Childers & Paik, 2009;Christie & Gentner, 2010;Gentner, Anggoro, & Klibanoff, 2011;Gentner & Namy, 1999;Haryu, Imai, & Okada, 2011;Namy & Gentner, 2002). For example, Gentner, Loewenstein, and Hung (2007) taught 3-, 4-, and 5-year-old children to identify novel object parts; children were shown a novel standard figure, told that "this one has a blicket," and asked to say which of two other figures also had a "blicket."…”
Section: Methodsmentioning
confidence: 99%
“…For example, in structural alignment models of similarity matching in non-linguistic domains (see Gentner, 1983Gentner, , 1989, the process of analogy required for generalisation is facilitated when the instances being compared are similar on any dimension. In language acquisition, crosssituational (and thus cross-constructional) similarity matching is highly likely to play a role in the acquisition of the meaning of novel words and, may in fact, be required in order for the Competing constructions 27 child to converge on the correct meaning (Childers & Paik, 2009). We simply extend this mechanism to the acquisition of form-meaning mappings.…”
Section: Competing Constructions 26mentioning
confidence: 99%
“…Comparison is particularly effective at highlighting the relational information necessary for learning verbs and other relational terms (Childers in press;Childers and Paik 2009;Gentner and Namy 2004;Haryu, Imai, and Okada in press;Pruden et al 2008). For example, Childers (in press) found that 2 2 1 -year-olds were better at learning novel verbs if they compared multiple instances that varied in their specific details.…”
Section: How Analogical Processing Supports Language Learningmentioning
confidence: 99%